2016
DOI: 10.1093/jamia/ocw145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of commercial computerized provider order entry (CPOE) and clinical decision support systems (CDSSs) on medication errors, length of stay, and mortality in intensive care units: a systematic review and meta-analysis

Abstract: Critical care settings, both adult and pediatric, involve unique complexities, making them vulnerable to medication errors and adverse patient outcomes. The currently limited evidence base requires research that has sufficient statistical power to identify the true effect of CPOE implementation. There is also a critical need to understand the nature of errors arising post-CPOE and how the addition of CDSSs can be used to provide greater benefit to delivering safe and effective patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 50 publications
1
111
0
7
Order By: Relevance
“…There is some evidence that e‐prescribing systems do reduce medication errors and adverse events, although assessment is complicated by variation in the software systems, decision support facilities, intensive care focus, alert systems and utilisation . A recent meta‐analysis of studies investigating the effect of e‐prescribing and clinical information systems in intensive care units identified no significant effect on medication errors in studies of adult patients . Administration errors with IV medications in particular present a risk to critical care patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that e‐prescribing systems do reduce medication errors and adverse events, although assessment is complicated by variation in the software systems, decision support facilities, intensive care focus, alert systems and utilisation . A recent meta‐analysis of studies investigating the effect of e‐prescribing and clinical information systems in intensive care units identified no significant effect on medication errors in studies of adult patients . Administration errors with IV medications in particular present a risk to critical care patients .…”
Section: Discussionmentioning
confidence: 99%
“…Critical care units utilise a variety of resources to reduce medication errors occurring in their patients . Technological solutions such as e‐prescribing and clinical information systems are frequently employed, although it remains unclear if these are effective interventions in adult practice . The complexity of patient care provided means that multiple interventions are likely to be required to address medication error risks – targeting multiple components of the medication process pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Prgomet et al's 2017 systematic review of CPOE in critical care, despite reporting an 85% overall error reduction, found no reduction on subgroup analysis of the four pediatric studies. 4 Two of these were the only PICUbased CPOE studies included in a recent systematic review of pediatric dosing errors-of which neither reported a significant change. [5][6][7] In PICU, infusion errors are of particular concern due to the routine use of multiple, high-risk medications across a 100-fold (<1->100 kg) weight range.…”
Section: Background and Significancementioning
confidence: 99%
“…20 Systematic reporting of TGEs, many of which are site-and system-specific, supports shared learning and system enhancement. 4,21,22 Diversity in TGE terminology is adding to the recognized difficulties in comparing medication error studies. 21,23 IntelliSpace Critical Care and Anesthesia (ICCA, Philips, United Kingdom) is a commercially available clinical information management system, widely used in both adult and pediatric hospitals in Ireland and the United Kingdom (Personal Communication, Philips, September 2019).…”
Section: Background and Significancementioning
confidence: 99%
“…[9][10][11][12][13][14] Parallel technological innovation has been proposed as a tool to combat errors in medical decision-making, 15 with significant advances already made. These include use of computerized order entry to decrease medication errors [16][17][18][19] and standardized "order sets" to reduce mistakes of omission. [20][21][22][23] Clinical decision support services (CDSSs) have been proposed and studied as a more generalized check against errors in patient care.…”
Section: Introductionmentioning
confidence: 99%